THE EFFECT OF TEST PREPARATION TOEFL READING TESTS - A.Elvi W Simanjuntak (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
AbstractThe main objective of this study was to see whether preparation influences the learners’ reading comprehension of TOEFL? Also as a subsidiary question, this study tried to find answer(s) to the following question: Does getting a high score imply enhancement in the reading comprehension ability? To this end, sixty EFL learners were selected to take part in a preparation program in which they were instructed different techniques and strategies to deal withthe reading section of TOEFL tests. Although the participants' scores enhanced in the post tests. Generally, findings showed that the preparation effect was more visible on performance of the TOEFL reading test. The TOEFL preparation group on the TOEFL reading test.Key words: TOEFL,test preparation,reading